THE UTILIZATION OF FUEL DIESEL EMULSION AS A RESERVE SOURCE OF DIESEL FUEL FOR INDONESIAN WAR SHIPS - Abdul Rahman; Dwi Kumara; Wawan Kusdiana; Anton Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
By the development of the time, diesel fuel is made from petroleum which is decreasing in number. Besides that, the emissions produced from burning diesel fuel can also cause air pollution. One of the methods used to minimize the use of diesel fuel and air pollution is by using emulsion fuel. therefore, a precautionary measure is required in preparing a reserve fuel source for Indonesian war ships. And one of the options is with emission diesel fuel. From the results of laboratory trials there was an increase in density, viscosity, flash point, cetane and TAN numbers and a decrease in residue, Lower Heating Value and calorific value. The performance test results show an increase in SFOC and thermal efficiency, but the power, torque and BMEP have decreased. So, it can be concluded that the emulsion HSD has decreased performance but can reduce emissions from the combustion process. So, it is hoped that emission diesel fuel can be used as an alternative as well as a solution to the limitations of diesel fuel in the future, so that it can support tni al operations in the future. Keywords : Diesel fuel , diesel fuel emulsion, reserve fuel, Indonesian Navy Operations